GE_GERICHTE P/1188/2011 vom 31. Oktober 2013 - GE Cour de justice (2013)
ADMINISTRATION DES PREUVES; APPEL(CPP); ACTE D'ACCUSATION; DIFFAMATION; MENACE(DROIT PÉNAL) | CPP.389; CPP.329; CPP.329; CP.173; CP.180